The conditioning factors for high risk prenatal care: Integrative review (Research, Society and Development, 2021)
Introduction: Prenatal monitoring corresponds to monitoring the health of pregnant women, in order to risk in order to bring support and quality of life to the mother/fetus. Objective: To know the conditioning factors for high-risk prenatal care. Methodology: This is an integrative review, it also has a qualitative exploratory method. Results: It is noticed that the pregnant woman needs full care by specialists, with the right to individual and group consultations, at regular intervals until delivery. This assistance will be mainly so that the traced complications are remedied until the baby's birth. It is observed that not only the prevention of risks during pregnancy, but also that health promotion should be implemented aiming at welcoming these pregnant women and a more unique look, thus contributing to the tracking of conditioning factors and health education for these women. Final considerations: It is up to the multidisciplinary team, especially that of primary care, to know the factors of high-risk prenatal care and be able to identify and monitor in order to prevent further complications, taking actions that prioritize specialized and humanized care, also aiming to promote the empowerment of pregnant women through health education actions with the aim of reducing deaths due to high-risk prenatal care.